Extracerebral Tissue Damage in the Intraluminal Filament Mouse Model of Middle Cerebral Artery Occlusion - Vaas, Markus; Ni, Ruiqing; Rudin, Markus; Kipar, Anja; Klohs, Jan (Frontiers in Neurology, 2017)
Middle cerebral artery occlusion (MCAO) is the most common model of focal cerebral ischemia in the mouse. In the surgical procedure the external carotid artery is ligated, however, its effect on the tissue supplied by the vessel has so far not been described. C57BL/6 mice underwent 1 h of transient MCAO (tMCAO) or sham surgery. Multi-spectral optoacoustic tomography was employed at 30 min after surgery to assess oxygenation in the temporal muscles. Microstructural changes were assessed with magnetic resonance imaging and histological examination at 24 h and 48 h after surgery. Ligation of the ECA resulted in decreased oxygenation of the left temporal muscle in most sham-operated and tMCAO animals. Susceptible mice of both groups exhibited increased T2 relaxation times in the affected muscle with histological evidence of myofibre degeneration, interstitial edema and neutrophil influx. Ligatures had induced an extensive neutrophil-dominated inflammatory response. ECA ligation leads to distinct hypoxic degenerative changes in the tissue of the ECA territory, and to ligature-induced inflammatory processes. An impact on outcome needs to be considered in this stroke model.